An Ultrasound Assessed Extraction Combined with Ion-Pair HPLC Method and Risk Assessment of Nitrite and Nitrate in Cured Meat - Babiker Yagoub Abdulkair; Amin O. Elzupir; Abdulaziz S. Alamer (Journal of Analytical Methods in Chemistry)
An accurate IPC-UV method was developed and validated for the determination of nitrite (NI) and nitrate (NA) in meat products. The best separation was achieved on a phenyl-hexyl column (150 mm × 4.6 mm, 3 µm) with a mobile phase composed of 25% acetonitrile and 75% buffer (2 mM disodium hydrogen phosphate and 3 mM tetrabutylammonium bromide, pH = 4). Eluents were monitored at 205 nm. Linearity ranges were 1.86 × 10−6–7.5 µg·ml−1 and 0.09–5.0 µg·ml−1 for NI and NA, respectively. The correlation coefficients were greater than 0.999 for NI and NA. This method was applied to a number of processed meat products in Riyadh (n = 155). NI ranged from 1.78 to 129.69 mg·kg−1, and NA ranged from 0.76 to 96.64 mg·kg−1. Results showed extensive use of NI and NA; however, concentrations were within the legal limit of Saudi Arabia except for one sample. Further, the risk assessment and dietary exposure have been estimated for both NI and NA.